2010
DOI: 10.2514/1.43264
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Graphite Ablation in Nitrogen Flow, Part II: Further Numerical Analysis

Abstract: The ablative behavior of graphite heated in an inductively coupled plasma wind tunnel is analyzed using an integrated computational method to examine the probability value of nitridation reaction occurring at graphite surface. In this method, the plasma torch freestream condition at the entrance of the test chamber is evaluated by calculating the flows in the plasma torch. The thermal response of the graphite test piece is calculated by loosely coupling the thermochemical nonequilibrium fluid dynamics code and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The majority of our measurements were obtained at 1273 K; the average value for these is about 3 10 3 . This average is very similar to the reaction efficiencies reported by Suzuki et al [18,20] for their ICP graphite ablation experiments and is the value that produces the best agreement between experiment and modeling of those experiments [21]. Compared with our test conditions, most of their ICP experiments were conducted at higher temperatures (1822-2184 K), higher total pressure (10 kPa), and much higher N-atom concentrations (by 2-3 orders of magnitude).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The majority of our measurements were obtained at 1273 K; the average value for these is about 3 10 3 . This average is very similar to the reaction efficiencies reported by Suzuki et al [18,20] for their ICP graphite ablation experiments and is the value that produces the best agreement between experiment and modeling of those experiments [21]. Compared with our test conditions, most of their ICP experiments were conducted at higher temperatures (1822-2184 K), higher total pressure (10 kPa), and much higher N-atom concentrations (by 2-3 orders of magnitude).…”
Section: Discussionsupporting
confidence: 88%
“…The N-atom concentration at the stagnation point of the test specimens was computed for each test case using a thermochemical nonequilibrium computational fluid dynamics code [6]. From the computed N-atom densities and the measured sample mass losses, Suzuki et al [18] reported reaction efficiencies of about 2:5 10 3 to 3:2 10 3 over a temperature range of 1822-2184 K. More recent measurements by Suzuki et al [20] have extended the data to lower temperatures where they find a reaction efficiency of about 1:4 10 3 at 1400 K. Suzuki et al [21] have also performed further numerical modeling of their experiments and reported the best agreement between computed and measured carbon ablation when the nitridation efficiency is set to 3:2 10 3 . The reaction efficiencies determined by Suzuki et al [18][19][20][21] are similar to those of Goldstein [15] and are about 2 orders of magnitude lower than those obtained by Park and Bogdanoff [16] at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Because there is no contact between the heating element and working gas, the produced ICP flow is highly pure. This advantage and the high-enthalpy property make ICP flows the preferred sources to develop the thermal protection systems (TPSs) of reentry vehicles, study nitridation reactions on the ablator surfaces [1] , investigate variations of electron dynamics [2] , prepare nanoparticles of intermetallic compounds [3] , etc.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, because there is sufficient space and a stable environment in the vacuum chamber, precision measuring instruments can easily be set up in it and reliable experimental data can be acquired there for validation of numerical methods. On the other hand, if detailed flow properties inside the vacuum chamber can be obtained, they will be very useful for tentative analysis and determining correct flow parameters for further studies such as investigation of nitridation reactions occurring at a graphite surface [12] and simulation of the thermal response of an ablator [13] .…”
Section: Introductionmentioning
confidence: 99%